Visual Language and Communication in an Emerging Global Civilization: The Ascendance of the Image. - Benitez, Jorge (International Journal of the Humanities, 2009)
The digital revolution alone cannot account for a shift from the dominance of language and printed words to the rule of images. What drives the rise of a post-Gutenberg, post-literary culture? Literacy remains essential; but traditional grammar, syntax and national languages must compete with the image-based abbreviated communications of the Internet. In order to determine whether such a development is real or even worthy of consideration, one must look at the history of iconoclasm since Plato and analyze the power of images in an age of conflict between the Word--the mainstay of ideology and religion--and a consumerist culture that relies on instant recognition and offers no dogma beyond gratification. Although many thinkers in developing and industrialized countries mistrust the idea of civilization as a racist remnant of imperialism, it remains a useful concept when discussing degrees and scales of development that exceed the definition of culture. If civilization could be reevaluated in an expanded manner, then it could be argued that early twenty-first century humans participate in what is truly the first global civilization. Lastly, what comprises a post-literary culture and how does it challenge today's ideological extremism? Is the rise of multi-religious violence (no single faith has a monopoly on terrorism) related to the word-inspired violence of twentieth-century totalitarianism and its utopian promises? How do image-based consumer societies clash with twenty-first century iconoclasm? Does this emerging global civilization have the potential to produce anything of depth at a time of diminishing resources and increasingly lethal fanaticism? This paper will consider these questions in order to offer a perspective based on the visual arts and the role of the image and visual language in communications.